Effect of Sclerotinia sclerotiorum culture filtrate on seed germination and seedling vigour of Indian mustard (Brassica juncea cv. Rohini) - Pankaj Sharma; PD Meena; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
Culture filtrate of 25 Sclerotinia sclerotiorum isolates isolated from infected Brassica plants grown in ninestates in India were tested for their effect on germination and seedling vigour of Indian mustard (Brassicajuncea) cultivar Rohini; fresh and dry mycelial weight of all isolates grown in Richard’s liquid medium werealso recorded. All geographical isolates showed considerable variability in fresh and dry mycelial weight.Compared to the control, filtrates of all isolates reduced seed germination and length of radicle and plumule.Isolates SR 15 and SR 03 significantly reduced the germination (53.5 and 53.3%) and gave the maximumpre-emergence mortality (46.9 and 46.7%). However, isolate SR 19 gave the maximum seed germination(83.4%) and minimum pre-emergence mortality (16.7%).